A Probabilistic Stochastic Income Distribution Model of Coal Mining Industry - Muhammad Kamran (Journal of Economics and Business Aseanomics (JEBA), 2021)
Coal mining is a profitable enterprise. It creates job opportunities, generates revenue, and attract the foreign investment of a country. However, coal mining faces some challenges. To address the allocation of capital related to coal mining, an approach has been made to improve the impact of coal mining industry on the economy of one of Indonesia most important coal producing region, south Kalimantan. A total of seven households of large-scale and small-scale mining are analyzed in the study. Various copula-based prediction probability models were established, and the exponential distribution function of household income distribution was obtained with maximum range by utilizing the application of Monte Carlo simulation. Moreover, this research spells out the importance of income distribution of various household dynamics which will help the policy maker in economic analysis and financial decisions related to various household categories